2017
DOI: 10.1002/ptr.5834
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Natural Products for the Treatment of Parkinson's Disease by Targeting the Autophagy-Lysosome Pathway: A Systematic Review

Abstract: The autophagy-lysosome pathway (ALP) is a primary means by which damaged organelles and long-lived proteins are removed from cells and their components recycled. Impairment of the ALP has been found to be linked to the pathogenesis of Parkinson's disease (PD), a chronic neurodegenerative disorder characterized by the accumulation of protein aggregates and loss of dopaminergic neurons in the midbrain. In recent years, some active compounds derived from plants have been found to regulate the ALP and to exert neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 79 publications
0
31
0
1
Order By: Relevance
“…One of the biological contributors to neurodegeneration and cognitive aging is chronic neuroinflammation. Accordingly, plant extracts with anti‐inflammatory properties have been extensively studied in relation to their potential use in treating cognitive decline (da Costa, Cavalcanti, de Queiroz, & de Azevedo, ; Kure, Timmer, & Stough, ; Meeusen & Decroix, ; Shal, Ding, Ali, Kim, & Khan, ; Wang et al, ). Bhattacharya and Bhattacharya () reported that 14‐day administration of devil's claw extract (100 and 200 mg/kg) stimulated, in a dose‐dependent manner, rat cortex superoxide dismutase, catalase, and glutathione peroxidase activities, with a concomitant reduction of tissue lipid peroxidation.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…One of the biological contributors to neurodegeneration and cognitive aging is chronic neuroinflammation. Accordingly, plant extracts with anti‐inflammatory properties have been extensively studied in relation to their potential use in treating cognitive decline (da Costa, Cavalcanti, de Queiroz, & de Azevedo, ; Kure, Timmer, & Stough, ; Meeusen & Decroix, ; Shal, Ding, Ali, Kim, & Khan, ; Wang et al, ). Bhattacharya and Bhattacharya () reported that 14‐day administration of devil's claw extract (100 and 200 mg/kg) stimulated, in a dose‐dependent manner, rat cortex superoxide dismutase, catalase, and glutathione peroxidase activities, with a concomitant reduction of tissue lipid peroxidation.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Documents reported that autophagy was wildly involved in variety of human diseases, such as cancer, inflammatory diseases, Parkinson disease, cardiovascular Disease, diabetes mellitus [42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Сегодня выявлены прямые взаимосвязи между мутациями в генах белков, запускающих митофагию (PINK1, Parkin, DJ-1), и наследственными нейродегенеративными заболеваниями [66,67]. Поýтому в последние годы идет активный поиск способов и средств регуляции аутофагии и митофагии [68][69][70]. В ýтом плане активно исследуются различные растительные продукты [70,71], изучаются ýффекты физических нагрузок и голодания [47,68,72], а также разрабатываются препараты с направленным на митохондрии действием [73].…”
Section: рисunclassified